A silver alginate paste dressing in the management of non-malignant wounds with signs of infection in oncology patients an observational prospective case series. Issue 3 (2021) - Nicodeme, Marguerite; Cheron, Maxime; Kriegel, Irène; Jaimes, Henry; Fromantin, Isabelle
No abstract available